Las vías indígenas de la occidentalización - Juan Carlos Estenssoro (Mélanges de la Casa de Velázquez)
This article is part of a history of the expression «language» in general. It purports to clarify its European origins, its various meanings and usages, and the different concepts to which it was opposed, the chief being that of a mother tongue. In obedience to the principle of economy of means —consisting in the use of the smallest possible number of tongues to evangelise the greatest possible number of people— the notion of a lingua franca prevailed in America when in Europe that notion as applied to Latin or to Latin-derived languages that acquired the status of national tongues, was disappearing. In the colonial world linguae francae came to be such through varying processes: some, like Nahuatl, served that purpose without bearing the label; others, like Quechua, were in fact the common term for language. Finally, we draw attention to the aspects that influenced the transformation of the uses and characteristics of these tongues (catechism, dictionaries and grammars, writing and printing).